A (re) produção do espaço na cidade de Campina Grande-PB: análise do conjunto habitacional Acácio Figueiredo - Sampaio, Tiago Marques (2019)
This research seeks to analyze the process of (re)production of Campina Grande’s city space through the study of the Acácio Figueiredo housing development from Minha Casa Minha Vida Program (PMCMV) intended for the popular classes, located in the city peripheral area. Its construction reproduces the same problems that are seen in other housing developments from previous national housing policies: built in the midst of a region with “urban voids”, far from where life actually takes place, using the same exhaustive pattern of architectural design and not including spaces intended for uses other than habitation. In this sense, the residential spaces, as they become inhabited, gained new forms and began to perform new functions, such as the residential spaces that have been adapted for commercial use. Given this, we seek to understand the factors that contributed to the production of housing in the peripheral areas of cities in recent context; identify the main forms of use and appropriation of space in the Acácio Figueiredo housing development, focusing especially in the construction of commercial establishments, places that provide services and spaces for collective use; and analyze the accessibility of the residents to the commercial areas. The analysis of spatial (re)production in Acácio Figueiredo, which takes place through the use and appropriation of space by residents, points out that although almost four years have passed since the delivery of houses, some types of commercial establishments necessary for daily life remain. nonexistent in the vicinity of the venture, such as pharmacies and banking agencies, as do public leisure spaces. In addition, the presence of commercial establishments in other neighborhoods in the consumption habits of residents interviewed, even in relation to products sold in Acácio Figueiredo, reflects the demand for more affordable prices and a greater variety of goods. The search highlights, therefore, the difficulties that the residents of the housing have due to the location and urban design of the venture, designed with strong monofunctional character, and the absence of municipal management facing of these questions.